BRAF V600E mutation associated with papillary high-grade serous ovarian cystadenocarcinoma in a 22q11.2DS patient - Maria Antonietta Castaldi; Nadia Petrillo; Carmine Selleri; Monica Ianniello; Anna Maria Della Corte; Eloisa Evangelista; Luigia De Falco; Roberto Sirica; Marika Casillo; Alessia Caleo; Alessandro Caputo; Pio Zeppa; et al. (Gynecologic Oncology Reports)
Objective: Ovarian cancers exhibit very heterogeneous genetic and genomic aberrations with various pathogenetic and prognostic values. Chromosome 22 abnormalities, including del(22q) and duplications, are genetic multisystemic disorders, most commonly affecting cardiovascular, immune, and gastrointestinal systems, while tumors are rarely reported. Methods: In this case report, we described a patient with 22q11.2 deletion syndrome who developed a papillary high-grade serous ovarian cystadenocarcinoma, and targeted- and whole-exome sequencing for genomic alterations identification and RNA-sequencing for transcriptomics analysis were performed. Results: Whole exome sequencing identified a B-Raf proto-oncogene, Serine/Threonine kinase (BRAF) V600E mutation, along with other somatic mutations, including BARD1 missense variant. Constitutional activation of the BRAF protein and its tumorigenic role in our patient was confirmed by upregulation of its downstream KRAS signaling pathway in tumor tissue compared to circulating cells. Conclusion: BRAF pathways could be involved in the molecular biology of papillary high-grade serous ovarian cystadenocarcinoma in a setting of 22q11.2 deletion syndrome.